Analisis Sistem Agribisnis Hulu ke Hilir Peternakan Goatday di Kecamatan Seyegan Kabupaten Sleman - Hafiizh Rayhan Wijaya; Siti Azizah (PT. PENERBIT TIGA MUTIARA, 2024)
Livestock agribusiness is an integral part of agricultural development as a subsector that fulfills society's animal protein needs. This research was carried out at the Goatday Farm located in Seyegan District, Sleman Regency on June 22 - August 20, 2023. This research aims to analyze the upstream-to-downstream agribusiness system of the Goatday farm, analyze the strategies that Goatday has implemented, and analyze the strategies that Goatday can implement in the future. The data sources in this research were obtained from key informants and follow-up informants. The key informant in this research is Mr. Muhammad Farid Akrom the owner of the Goatday farm, while further informants are Mr. Ahmad Fauzi and Mr. Hendri the person in charge of the Goatday farm, and Mr. Hermawan the partner of the Goatday breeder. The analysis used is descriptive analysis, Business Model Canvas (BMC), and SWOT analysis. The result of this research was that Goatday has implemented an agribusiness system on its farms that is integrated. Goatday has also implemented partnerships and has a well-systemized farm. Based on the SWOT analysis, the strategy that Goatday can implement in the future is to create an education-based farm and provide more training to staff and partners regarding efficient maintenance management.